How neo-Marxism creates bias in gender and migration research: evidence from the Philippines. - Dumitru, Speranta (Ethnic & Racial Studies, 2018)
The paper analyses migration flows from the Philippines in two gendered occupations: domestic helpers and computer programmers. The international division of labour theory claims that foreign investment determines migration from developing countries, especially of women, towards low-skilled gendered occupations in developed countries. This paper shows that the division of labour is neither gendered nor international in the predicted sense. For instance, data from Philippines Overseas Employment Agency shows that the theory is Eurocentric as Northern America and Europe are destinations for only 3 per cent of domestic workers’ flows. The paper argues that neo-Marxism creates bias in gender and migration research and hinders understanding of important gendered effects concerning migrants. Two examples of such gendered effects are highlighted here: the higher vulnerability to legislative change of migrant men employed as domestic workers in Italy and the higher penetration of women into computer programming in the migrant flows to the U.S.